Development of prose appreciation teaching materials based on experiential learning - Lazuardi, Dian Ramadan; Hamzah, Syukri; Arono, Arono (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Prose appreciation is a mandatory course taken by prospective primary school teacher education students in the first semester with a load of 2 credits. This research was carried out to develop Prose Appreciation teaching materials based on an experiential learning approach and to determine the validity and practicality of Prose Appreciation teaching materials based on an experiential learning approach. This research uses an R&D (research and development) approach, namely the Dick and Carey model. The data collection techniques used were interviews and questionnaires. Data analysis techniques used were interviews and questionnaires conducted qualitatively and quantitatively. The research results show that the Prose Appreciation teaching lesson based on the Experiential Learning approach is valid and practical for use in lectures. The linguistic validation results show that the Prose Appreciation teaching material is very valid for use with a score of 0.89. The validation results of the presentation and graphics obtained a figure of 0.77 in the valid category. Meanwhile, the content/material expert assessment obtained a figure of 0.87, which is in the valid category. Furthermore, the small group trial showed that the Prose Appreciation teaching material was practical to use and the large group trial showed that the Prose Appreciation teaching material was very practical to use.